ナンキョク ショウワキチ ムデントウ ノ パネル コウセイ ヨウソ ノ ケイネン ヘンカ ト タイキュウセイ - 平山, 善吉; ヒラヤマ, ゼンキチ; 半貫, 敏夫; ハンヌキ, トシオ; 坪内, 信朗; ツボウチ, ノブオ; 高橋, 拡; タカハシ, ヒロム; Hirayama, Zenkichi; Hannuki, Toshio; Tsubouchi, Nobuo; Takahashi, Hiromu (2002)
P(論文) 1997年に昭和基地から持帰った昭和基地無電棟は、わが国初の木質パネル構造によるプレハブ建築の1つである。1981年4月に第1次越冬隊用の居住棟が持帰られ、翌1982年に性能評価試験が行われた。そして今回40年ぶりに第1次越冬隊用の無電棟を持帰り、構成材料、部材の性能試験が行われた。無電棟のパネルの構成は、枠材両面に合板を張り、中空部に発泡ポリスチレンを充填した軽量・高断熱パネルである。性能試験は、合板ラミナの接着力、合板と枠材間の接着力、パネル枠材の強度、断熱材の熱伝導率、パネルの熱貫流量について行った。また今回の試験結果と1982年のデータの比較も行った。性能試験の結果より、南極で40年経過した無電棟の構成材料、部材の性能は一部を除いて、ほとんど変化していないことが認められた。 The wireless hut built in 1957 at Syowa Station brought back to Japan in 1997 is one of the first wooden panel-structured and prefabricated buildings in our country. In April 1981, the living hut for the first wintering party was brought back and evaluated by a performance test in 1982. This time, the wireless hut for the first wintering party was brought back after 40 years. We tested the performance of the construction material and framework members. The wireless hut panels were formed by adhesion of plywood to both surfaces of the frame material and injecting expanded polystyrene into the hollow part so that the panels are light-weight and have high heat resistance. We conducted performance tests on the adhesive strength of plywood and frame material, strength of the panel frame material, thermal conductivity of heat insulating material, and heat transmission flow rate of panel, and compared those results with research done in 1982. From the performance test results, we concluded that the construction material and framework members of the wireless hut being 40-year old at Syowa Station in the Antarctic have hardly changed, except for a few parts. departmental bulletin paper